The Tenchini's collection: a forensic anthropometric legacy of 19th century Parma, Italy - Laura Donato; Roberto Toni; Alessandro Porro; Marco Vitale; Fulvio Barbaro; Rossana Cecchi (Oxford University Press, 2019)
A group of 19th century inmates dead in the prison of Parma are the protagonist of an incredible scientific collection. Lorenzo Tenchini started the creation of this collection and dedicated his work and his studies to its completeness. Anatomist and academic, Lorenzo Tenchini (1852-1906) dedicated his scientific studies to macroscopic anatomy, particularly about central nervous system and its correlation with psychic function. In 1881 he became ordinary professor in Normal Human Anatomy at the University of Parma dedicating himself to the study of the anatomical organization of the brain and psychic and social disturbs. During the study of the skulls and brains of psychotic patients and the deformations of skulls belonging to patients admitted in the Hospital of Brescia, he started a collaboration with Alessandro Cugini (1829-1913), founder of the Institute of Legal Medicine at the University of Parma. Tenchini realized an anatomical collection, preserved today in the Museum of Biomedicine of the University of Parma. This collection represents the masterpiece of his research carried out during his academic activity and still a unicum in the western world, as there are no similar collection assembling such a multidisciplinary information. The peculiarity of this collection is due not only to the scientific interest of the anatomic samples and their full clinical documentation, but also to the methods employed in order to realize it. At the end of the 19th century, as a student of Cesare Lombroso (1835-1909), Tenchini based his work on the study of the face, the skull and brain of each dead inmate of Parma's prison or Colorno's mental hospital. These individuals as protagonists of Tenchini's collection, leave a legacy identifiable as scientific heritage. Their skulls and brains, the reproduction of their faces through ceroplastic and other anatomical samples treated with other techniques, are accompanied by an autoptic and psychiatric full documentation, allowing the collection to be complete with every aspect related to the inmates studied. Through his work, a comparison between different kind of studies, such as psychiatry, psychology, neurology, legal medicine and anthropology, is suitable in scientific research to be realized. Moreover, data come from a forensic context: this allows a comparison with different methodologies employed in modern age by forensic expertise such as the comparison between modern and ancient medical diagnostic technique. This masterpiece represents Tenchini's neuroanatomical research on behaviour and set a pioneering step in the history of biomedical science allowing further multidisciplinary studies.